2021
DOI: 10.1294/jes.32.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel rice fermented extract on gastric ulcers in horses

Abstract: Gastric ulcers cause appetite loss, poor body condition, and colic in horses. This study investigated the protective effect of a rice fermented extract on the gastric mucosa in 17 healthy Thoroughbreds. For one month, horses in the rice fermented extract (nine horses) and control (eight horses) groups were orally administered a rice fermented extract (100%; 0.2 ml/kg, SID) and tap water (0.2 ml/kg), respectively. Gastric endoscopic images were obtained before and one month after rice fermented extract administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A micronized, fermented and pasteurized soy product was evaluated in a population made up of a majority of racehorses, and was protective against increased ESGD scores compared to the pollard control fed for 30 days [ 203 ]. A non-blinded study found that one month’s supplementation with a fermented rice extract significantly improved naturally occurring ESGD scores compared to tap water [ 204 ]. Aloe vera fed at 17.6 mg/kg PO BID for 28 days was found to reduce naturally occurring ESGD scores and heal lesions in 56% of 19 horses in one study without a control group [ 136 ].…”
Section: Preventionmentioning
confidence: 99%
“…A micronized, fermented and pasteurized soy product was evaluated in a population made up of a majority of racehorses, and was protective against increased ESGD scores compared to the pollard control fed for 30 days [ 203 ]. A non-blinded study found that one month’s supplementation with a fermented rice extract significantly improved naturally occurring ESGD scores compared to tap water [ 204 ]. Aloe vera fed at 17.6 mg/kg PO BID for 28 days was found to reduce naturally occurring ESGD scores and heal lesions in 56% of 19 horses in one study without a control group [ 136 ].…”
Section: Preventionmentioning
confidence: 99%
“…The NF-κB induces the production of a large number of cytokines and growth factors, which further activates NF-κB, exacerbating the inflammatory response [7]. Inhibiting the NF-κB signaling pathway improves ethanol-induced gastric ulcers in rats [8]. Furthermore, NF-κB activation promotes inflammation and carcinogenesis of gastric mucosal epithelial cells during infection with H. pylori.…”
Section: Introductionmentioning
confidence: 99%